Dynamic viscoelastic measurement of gelatin gel and porcine liver specimen by micro-MRE - Hayato SUZUKI; Satoshi YAMADA; Mototeru GOTO; Shigeru TADANO (Nihon Kikai Gakkai ronbunshu, 2017)
This study aimed to measure a viscoelastic property of gelatin gels and porcine liver by the magnetic resonance elastography using micro-magnetic resonance imaging (micro-MRE). In the experiments, gelatin gel specimens (90 × 70 × 50 mm) made of gelatin solution with 5, 7, 10, 12, and 15 wt% concentration were examined under excitation with longitudinal waves in frequency of 50-250 Hz and amplitude of 0.5 mm. The viscoelastic modulus was obtained as storage shear modulus G’ and loss shear modulus G”. As a result, G’ values increased with the concentration and the excitation frequency. G” value was much smaller than G’. Double-layer specimens composed of 5 and 15 wt% gelatin gels were also examined. The average of G’ in each concentration gel in the double-layer specimens showed no significant difference from the single-material specimens with the same concentration. Furthermore, a porcine liver specimen (150 × 50 × 30 mm) were examined; however, the specimen were not vibrated and the displacement distribution in the specimen was not observed. When porcine liver specimens were embedded in the 15 wt% gel (70 × 70 × 50 mm), the specimens were vibrated deeply and G’ and G” of the liver and gel regions were obtained. As a result, G’ of the gel region was almost the same as the value of the gel specimens. G’ of the liver region increased with the excitation frequency as well as the gel specimens. The viscoelastic modulus of the porcine liver could be measured by embedding it inside gelatin gel using the micro-MRE system. This study demonstrated the application of the MRE system as the dynamic viscoelasticity measurements of gelatin gel and liver specimen.